Monkeypox Virus Outbreak 2022: Assessment of Knowledge Among Healthcare Workers in Two Countries—India and Saudi Arabia - Sachin Naik; Sajith Vellappally; Abdulaziz Abdullah Al Kheraif; Majed M. Alsarani; Santhosh Basavarajappa; Raghad Khalid Alhassoun; Mohamed Hashem; Hassan Fouad; Murtaza Saleem; Faisal Ali M Asiri; Meshal Saeed Mohammed Awaiyer (International Journal of Clinical Practice)
Conclusion: HCWs in both countries had moderate to poor knowledge about the monkeypox outbreak. This might be because monkeypox is not prevalent in these countries. More education is needed to improve HCWs knowledge about monkeypox infection.